Kecernaan Kalsium dan Fosfor, pH gizzard, Kadar Air Ekskreta dan Digesta pada Ayam Petelur yang Diberi Ukuran Partikel Batu Kapur Berbeda dan Enzim Fitase: Digestibility of Calcium and Phosphorus, Gizzard PH, Excreta and Digesta Moisture Content in Laying Hens on Different Limestone Particle Size and Phytase - Rushafarani, Yurida; Sumiati; Nahrowi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to determine the coefficient of total calcium and phosphorus digestibility effects from limestone as a source of calcium and the effect of phytase enzymes on laying hens. This study used 180 Hy-line Brown laying hens aged 75 weeks. The experimental design used was a 2x2 factorial complete randomized design (CRD) with 9 replications. The first factor was limestone particle size, i.e., P1 = limestone flour and P2 = limestone granules, and the second factor was phytase enzyme dose, i.e., Q1 = 0 FTU and Q2 = 1000 FTU. The observed variables were gizzard pH, excreta moisture content (MC), digesta MC, calcium and phosphorus digestibility using two samples and ileal digestibility. The results showed that the digestibility of calcium from limestone flour was significantly different compared to limestone granules at P<0.05. The phytase addition and the interaction with limestone particle size did not affect gizzard pH, total and ileal digestibility of calcium and phosphorus. Excreta and digesta MC had a significant effect on the particle size of limestone, the highest MC was limestone granules compared to flour (P<0.001). The addition of phytase had an effect on reducing excreta MC (P< 0.001). There was interaction between limestone size and phytase in excreta and digesta MC. The conclusion of the research was that laying hens were more efficient in digesting calcium from limestone flour compared to limestone granules. Phytase could reduce excreta and digesta MC. Key words: calcium, digestibility, limestone, particle size, phytase